Ethiopia's Strategic Influence: Shaping Geopolitical and Economic Dynamics in the Horn of Africa (Asian Journal of Social Science Studies, 2025)
Ethiopia, a country with considerable geopolitical and historical significance, stands at a critical juncture in the Horn of Africa. This paper explores Ethiopia’s potential role as either a driving force for regional progress or a source of instability. Through an analysis of Ethiopia’s ambitious infrastructure projects, including the Grand Ethiopian Renaissance Dam (GERD), and its diplomatic strategies, the study examines the country’s impact on the region. While Ethiopia’s investments in infrastructure and energy, such as the Ethiopia-Djibouti Railway, suggest a move towards regional cooperation and economic development, tensions with neighboring countries particularly concerning the GERD and ongoing historical disputes underscore the challenges Ethiopia faces in promoting stability. The country’s infrastructural initiatives reflect its commitment to improving connectivity and fostering economic integration within the Horn of Africa. Furthermore, Ethiopia’s goal to become a regional energy powerhouse via the GERD offers both opportunities and risks, especially in its relationships with downstream countries like Egypt and Sudan. These issues highlight the complex balance Ethiopia must maintain between pursuing its national interests and encouraging regional collaboration. The paper also discusses Ethiopia’s diplomatic efforts, focusing on its leadership role within the African Union and the Intergovernmental Authority on Development (IGAD), as it manages internal conflicts and external pressures. Ultimately, the study concludes that Ethiopia’s future in the Horn of Africa will depend on its ability to maintain domestic stability while navigating diplomatic challenges and building cooperative relationships with its neighbors.